A Subsidized Healthy Food Prescription Program for Adults With Type 2 Diabetes Who Are Experiencing Food Insecurity: Protocol for a Randomized Controlled Trial. (7th June 2021) - Dunn, Sharlette; Olstad, Dana; Beall, Reed F; Spackman, Eldon; Lipscombe, Lorraine; Williams, Kienan; Oster, Richard; Scott, Sara; Zimmermann, Gabrielle; McBrien, Kerry A; Steer, Kieran JD; Chan, Catherine B; et al.
Abstract: Objectives: It is vital for individuals with type 2 diabetes (T2DM) to adhere to a healthy dietary pattern to maintain optimal blood glucose levels and overall health. Increasing costs of healthy foods, however,  are a barrier to maintaining healthful dietary patterns, particularly for individuals with T2DM who are experiencing food insecurity. Poor diet quality may result in difficulties maintaining optimal blood glucose levels, leading to higher rates of diabetes complications, and increased acute care usage and costs. Although the adverse impacts of food insecurity on maintaining optimal blood glucose levels are well documented, effective strategies to this among individuals with T2DM are lacking. One approach is providing subsidies to purchase healthy foods through subsidized healthy food prescription programs. These programs may help reduce food insecurity and improve diet quality, thereby improving blood glucose levels and reducing diabetes complications over time. Methods: A parallel group randomized controlled trial will examine the effectiveness of a subsidized healthy food prescription program compared to a healthy food prescription alone in improving average blood glucose levels (primary outcome), and other secondary outcomes among 404 adults who are experiencing food insecurity and persistent hyperglycemia. The subsidized healthy food prescription program consists of two core elements: 1) A one-time healthy food prescription pamphlet that outlines an evidence-based healthy dietary pattern; 2) A healthy food subsidy of $1.50/day/household member to purchase healthy foods in participating supermarkets for 6 months. At baseline and 6-month follow-up, participants will provide responses to sociodemographic and health-related items, and a variety of patient-reported outcomes. Biochemical and physical measurements will also be obtained. Results: The study's theory of change posits that reducing food insecurity and improving diet quality will be key mediators in improving blood glucose levels, which may reduce diabetes complications, and healthcare usage and costs over time. Conclusions: The results of this study will demonstrate if a subsidized healthy food prescription program results in meaningful changes in average blood glucose levels and other clinically relevant outcomes. Funding Sources: Alberta Innovates, Alberta Health Services.